Fiscal Policy. Locational Decisions, and Exchange Rates. (IMF Working Papers; Working Paper ;, 1989)
The paper distinguishes between three different channels through which fiscal policy changes may be transmitted to exchange rates. Based on both the balance of payments identity and empirical observations, it is argued that trade balances and exchange rates may be quite responsive to changes in the relative attractiveness of locating production facilities or storing other 'taxable' forms of wealth in different countries. Recognition that fiscal policy has a major influence on asset location decisions may thus be very important for understanding the behavior of exchange rates.